2013
DOI: 10.1016/j.tem.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

AMPK: mediating the metabolic effects of salicylate-based drugs?

Abstract: Salicylates are among the oldest and most widely used medications, used to reduce fever, pain and inflammation. The major oral salicylates are aspirin and salsalate, both of which are rapidly metabolized to salicylate in vivo. Due to its acetyl group, aspirin irreversibly inhibits cyclooxygenases and thus blocks platelet aggregation, while salsalate has been used for treatment of inflammatory diseases such as rheumatoid arthritis. Recently, beneficial effects of salicylates in type 2 diabetes and cancer have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 58 publications
2
58
0
Order By: Relevance
“…Interestingly, salicylates and other nonsteroidal anti‐inflammatory drugs were also shown to extend lifespan of yeast and fly through inhibition of tryptophan uptake (Danilov et al, 2015; He et al, 2014). Salicylates have also been shown to activate the adenosine monophosphate‐activated protein kinase (AMPK) (Hawley et al, 2012; Steinberg, Dandapani, & Hardie, 2013). This may in part explain why they held promise as treatments to improve insulin resistance and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, salicylates and other nonsteroidal anti‐inflammatory drugs were also shown to extend lifespan of yeast and fly through inhibition of tryptophan uptake (Danilov et al, 2015; He et al, 2014). Salicylates have also been shown to activate the adenosine monophosphate‐activated protein kinase (AMPK) (Hawley et al, 2012; Steinberg, Dandapani, & Hardie, 2013). This may in part explain why they held promise as treatments to improve insulin resistance and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that aspirin may significantly impact cellular metabolism (Steinberg et al, 2013;Kamble et al, 2015). Furthermore, studies have suggested that SIRT1 or AMPK may contribute to the anticancer activity of aspirin mediating its ability to inhibit cell growth (Motoshima et al, 2006;Liu et al, 2009;Kumazaki et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action most commonly associated with salsalate is the direct repressing effect of salicylate on inhibitor of nuclear factor κ-B kinase subunit β (IKK-β) to reduce inflammation (11-13). However, the concentration of salicylate used in these studies nonspecifically inhibits many protein kinases through direct competition with their ATP binding sites (16)(17)(18). In contrast to kinase inhibition, salicylate has also been shown to directly activate AMPK, a metabolicsensing enzyme important for regulating inflammation (19), liver lipid metabolism (20), and brown fat thermogenesis (21,22).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…Because the dose of salicylate used in this study results in serum concentrations of salicylate more than double the clinical levels after the oral intake of salsalate (~2.4 mmol/L compared with ~1.0 mmol/L, respectively) we hypothesized that the AMPK-β1-independent effects may have been a result of off-target kinase inhibition (16)(17)(18).…”
mentioning
confidence: 99%